2015
DOI: 10.1186/s13071-015-1259-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the mouse model identify strain variability as a major determinant of disease outcome in Leishmania infantum infection

Abstract: Background: Visceral leishmaniasis is a severe and potentially fatal disease caused by protozoa of the genus Leishmania, transmitted by phlebotomine sandflies. In Europe and the Mediterranean region, L. infantum is the commonest agent of visceral leishmaniasis, causing a wide spectrum of clinical manifestations, including asymptomatic carriage, cutaneous lesions and severe visceral disease. Visceral leishmaniasis is more frequent in immunocompromised individuals and data obtained in experimental models of infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Following the MRP physicochemical characterization, the formulation was tested on C57BL/6 mice model. Inbred mice, including C57BL/6 and BALB/c, have widely been used to assess early indications of microbicide safety profile and generally provide reproducible results. Prior to any MRP exposure, the diestrus-like state of mice treated with Depo-Provera was assessed. Thus, the mice CVL were constantly collected, for up to 9 days, and analyzed for evidence of nucleated and cornified squamous epithelial cells and polymorph nuclear leukocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Following the MRP physicochemical characterization, the formulation was tested on C57BL/6 mice model. Inbred mice, including C57BL/6 and BALB/c, have widely been used to assess early indications of microbicide safety profile and generally provide reproducible results. Prior to any MRP exposure, the diestrus-like state of mice treated with Depo-Provera was assessed. Thus, the mice CVL were constantly collected, for up to 9 days, and analyzed for evidence of nucleated and cornified squamous epithelial cells and polymorph nuclear leukocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, although infected spleen cells produced more NO than uninfected ones, both the LIC and LII strains were still able to survive and multiply within the host, increasing parasite load at 60 dpi, especially in the case of the LII strain. Marques and collaborators (2015) [ 36 ] have reported that LII parasites were able to survive high amounts of NO added to the culture. Regarding ARG activity, lower urea production was observed in the spleen and liver of infected animals when compared to uninfected controls.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although infected spleen cells produced NO more than uninfected ones, both LIC and LII were still able to survive and multiply within the host, increasing parasite load at 60 dpi, especially in the case of LII. Marques and collaborators (2015) [34] have reported that LII parasites were able to survive high amounts of NO added to the culture.…”
Section: Discussionmentioning
confidence: 99%
“…As published studies have shown that isolates of L. infantum belonging to the same zymodeme, which may present different sensitivities to the host’s immune response, which may be related to parasite virulence factors [27] . There are studies indicating that differences in infectivity between L. infantum strains could be related to modulation by the parasites of the expression of L-arginine metabolic enzymes during mouse infection [34] . Studies about differences between parasites from different geographic regions are needed.…”
Section: Discussionmentioning
confidence: 99%